KUALITAS PERAIRAN DAN KEANEKARAGAMAN MIKRO ALGA DI DANAU DENDAM UNTUK MENYUSUN STRATEGI PENGELOLAAN KAWASAN TWA DANAU DENDAM - Wijnana, Adhika Putra Agra; Martono, Agus; Martono, Dede; Susatya, Agus; Yansen, Yansen (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Lake Dendam is never a loticwaters with lots of human activities around the area. The high human activity around the waters has an impact on the quality of the waters and the organisms in the vicinity. This observation was carried out to obtain an up-to-date picture of water quality and micro-algae biodiversity in Revenge Lake for developing sustainable management strategies. Tests were carried out on the chemical and physical quality of the waters, and the biodiversity of microalgae which were then processed into an area management strategy. The results of the water quality test showed slightly polluted conditions with values of dissolved oxygen (DO), chemical oxygen demand (COD), total suspended solid (TSS), and phosphate which were still outside the water quality standards. However, conditions that can still be tolerated are peat waters. The microalgae biodiversity test showed the dominance and diversity of microalgae genera in the waters. The dominant genus is Nitzchia sp. From these results obtained six sustainable management strategies for Revenge Lake. Keywords : Biodiversity, Dendam Lake, microalgae, water quality